Changes in ginsenoside compositions and antioxidant activities of hydroponic-cultured ginseng roots and leaves with heating temperature - Cho Rong Hwang; Sang Hoon Lee; Gwi Yeong Jang; In Guk Hwang; Hyun Young Kim; Koan Sik Woo; Junsoo Lee; Heon Sang Jeong (Journal of Ginseng Research, 2014)
Background: This study evaluated changes in ginsenoside compositions and antioxidant activities in hydroponic-cultured ginseng roots (HGR) and leaves (HGL) with heating temperature. Methods: Heat treatment was performed at temperatures of 90°C, 110°C, 130°C, and 150°C for 2 hours. Results: The ginsenoside content varied significantly with heating temperature. The levels of ginsenosides Rg1 and Re in HGR decreased with increasing heating temperature. Ginsenosides F2, F4, Rk3, Rh4, Rg3 (S form), Rg3 (R form), Rk1, and Rg5, which were absent in the raw ginseng, were formed after heat treatment. The levels of ginsenosides Rg1, Re, Rf, and Rb1 in HGL decreased with increasing heating temperature. Conversely, ginsenosides Rk3, Rh4, Rg3 (R form), Rk1, and Rg5 increased with increasing heating temperature. In addition, ginsenoside contents of heated HGL were slightly higher than those of HGR. The highest extraction yield was 14.39% at 130°C, whereas the lowest value was 10.30% at 150°C. After heating, polyphenol contents of HGR and HGL increased from 0.43 mg gallic acid equivalent/g (mg GAE eq/g) and 0.74 mg GAE eq/g to 6.16 mg GAE eq/g and 2.86 mg GAE eq/g, respectively. Conclusion: Antioxidant activities of HGR and HGL, measured by 1,1-diphenyl-2-picrylhydrazyl and 2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid radical scavenging ability, increased with increasing heating temperature. These results may aid in improving the biological activity and quality of ginseng subjected to heat treatments.